Good practice guide to internal flexibility policies in companies - Goudswaard, Anneke; Oeij, Peter; Brugman, Tony; de Jong, Tanja (Dublin, 2009)
"This report sets out to contribute to the present debate on the need for European companies and their workers to become more flexible and adaptable in the face of ongoing economic change and business restructuring. The guide should therefore provide useful and practical tips for company-level actors concerning the potential benefits of developing more flexible internal workplace policies. Equally, it has been developed to assist practitioners and social partners wishing to review and/or learn more about developing such initiatives."